14.8k views
4 votes
If f(x)=3x+5 and g(x)=-2x^2-5x+3, find (f+g) (x)

If f(x)=3x+5 and g(x)=-2x^2-5x+3, find (f+g) (x)-example-1

2 Answers

6 votes


f(x)=3x+5,\ g(x)=-2x^2-5x+3\\\\(f+g)(x)=f(x)+g(x)=(3x+5)+(-2x^2-5x+3)\\\\=3x+5-2x^2-5x+3=-2x^2+(3x-5x)+(5+3)=-2x^2-2x+8\to\boxed{C.}

User Shawn Andrews
by
4.9k points
7 votes
Given :-

... f(x) = 3x + 5

... g(x) = -2x² - 5x + 3

Find (f + g)(x)

... f(x) + f(g)

... 3x + 5 + ( -2x² - 5x + 3 )

... 3x + 5 - 2x² - 5x + 3

Combining like terms :-

... -2x² + 3x - 5x + 5 + 3

... -2x² - 2x + 8

Hence, the answer is -2x² - 2x + 8 or option ( c ) .
User OscarVGG
by
5.0k points